(a-b)的三次方=-___ (b-a)的三次方(a-b)的三次方=-___ (b-a)的三次方(a-b)的2n-1次方=____(b-a)的2n-1次方

来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/02 04:38:13
(a-b)的三次方=-___(b-a)的三次方(a-b)的三次方=-___(b-a)的三次方(a-b)的2n-1次方=____(b-a)的2n-1次方(a-b)的三次方=-___(b-a)的三次方(a

(a-b)的三次方=-___ (b-a)的三次方(a-b)的三次方=-___ (b-a)的三次方(a-b)的2n-1次方=____(b-a)的2n-1次方
(a-b)的三次方=-___ (b-a)的三次方
(a-b)的三次方=-___ (b-a)的三次方
(a-b)的2n-1次方=____(b-a)的2n-1次方

(a-b)的三次方=-___ (b-a)的三次方(a-b)的三次方=-___ (b-a)的三次方(a-b)的2n-1次方=____(b-a)的2n-1次方
(a-b)的三次方=-(b-a)的三次方
(a-b)的2n-1次方=-(b-a)的2n-1次方


-3(a-b)^6×a²(b-a)³
=-3(a-b)^6×a²[-(a-b)]³
=3(a-b)^6×a²(a-b)³
=3a²(a-b)^9
请采纳答案,支持我一下。